2023
DOI: 10.2503/hortj.utd-386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Regulators on Forced Sprouting and Growth of Ginger

Abstract: In Taiwan, the early harvesting of young ginger is a cultivation technique for domestic ginger, which can be harvested early by forced sprouting. At present, ethylene is used as the sprouting agent. Despite its favorable sprouting effect, the technique can still be improved. Experimental results revealed that 1% citric acid, 300-ppm and 450-ppm ethephon treatments effectively facilitated the formation of 2.4, 2.4, and 2.6 large buds (diameter of ≥ 1 cm), respectively, in the rhizome. The stems and leaves of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previously it has been demonstrated that spraying GA increased the shoot length of ginger and weight of ginger rhizome ( 64 ). Similarly, the yield of ginger rhizomes was significantly increased by the application of GA3 ( 65 , 66 ). In Po-VOC-exposed ginger plants, there was an upregulation in the expression of genes annotated with the Pfam domain for expansin C-terminal domain (PF01357), which can positively correlate with the growth enhancement in Po-VOC-exposed ginger plants as expansin proteins are involved in cell expansion and elongation ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been demonstrated that spraying GA increased the shoot length of ginger and weight of ginger rhizome ( 64 ). Similarly, the yield of ginger rhizomes was significantly increased by the application of GA3 ( 65 , 66 ). In Po-VOC-exposed ginger plants, there was an upregulation in the expression of genes annotated with the Pfam domain for expansin C-terminal domain (PF01357), which can positively correlate with the growth enhancement in Po-VOC-exposed ginger plants as expansin proteins are involved in cell expansion and elongation ( 67 ).…”
Section: Discussionmentioning
confidence: 99%